Spontaneous Synthesis and Electrochemical Characterization of Nanostructured MnO2 on Nitrogen-Incorporated Carbon Nanotubes. (19th January 2012) - Chen, Ying-Chu; Hsu, Yu-Kuei; Lin, Yan-Gu; Chen, Li-Chyong; Chen, Kuei-Hsien
Abstract : This paper investigated the layered manganese dioxide with hydrate (MnO 2 ⋅ x H 2 O ) deposits onto nitrogen-containing carbon nanotube (CNxNTs) as a hierarchical electrode for an energy-storage device. The dense and entangled CNxNTs were directly grown by microwave plasma-enhanced chemical vapor deposition (MPECVD) on a carbon cloth (CC), and subsequently used as a current collector. By controlling the pH value of KMnO4 precursor solution, and incorporating nitrogen into CNTs as a reducing agent, the MnO2 thin layer was uniformly fabricated on the CNxNTs at room temperature by using a spontaneous reduction method. The role of incorporation nitrogen is not only capable of creating active sites on the CNT surface, but can also donate electrons to reduce MnO 4 - to MnO2 spontaneously. From the measurements of cyclic voltammograms and galvanostatic charge/discharge, MnO2 /CNxNTs/CC composite electrodes illustrated excellent specific capacitance of 589.1 Fg -1 . The key factor for high performance could be attributed to the thin-layered MnO2 nanostructure, which resulted in the full utilization of MnO2 deposits. Hence, the hierarchically porous MnO2 /CNxNTs/CC electrodes exhibited excellent capacitive behavior for electrochemical capacitor application.